STRATEGI GURU PAI DALAM INTERNALISASI NILAI TOLERANSI BERAGAMA DI ERA DIGITAL: Studi Kasus di SMA Negeri 2 Bondowoso - Hidayati; Maimunah; Ansori (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2026)
The increasing phenomenon of religious intolerance among students shows that Islamic Religious Education (PAI) learning still faces challenges in effectively internalizing the value of tolerance, especially amidst the increasingly strong influence of digital media. Previous research has generally focused on the role of Islamic Religious Education teachers as moral role models or tolerance learning strategies, but has not explained much about the mechanisms of internalization of tolerance values that occur in the context of education and the digital era. This study aims to analyze the strategies of Islamic Religious Education teachers in internalizingthe value of religious tolerance, identifying the mechanisms of internalization of the values formed, and analyzing their implementation in the context of the digital era at State Senior High School 2 Bondowoso. The research uses a qualitative approach with a case study design based on the interpretivism paradigm and constructivism approach. Data were obtained through in-depth interviews, participant observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that the internalization of religious tolerance values occurs through four interrelated mechanisms, namely teacher role models as behavioral models, dialogic learning as a space for value construction, integration of values in learning materials and school culture as a social reinforcement system, and digital literacy as a mediating mechanism against external influences. These four mechanisms form an ecological-pedagogical model that explains that religious tolerance is not formed linearly through cognitive learning alone, but through interactions between teachers, students, the school environment, and digital spaces. This finding provides a theoretical contribution to the development of Islamic Religious Education studies based on the internalization of religious values and moderation in the digital era.